87Sr/86Sr isotope ratio and multielemental signatures as indicators of origin of European cured hams: The role of salt. (25th April 2018) - Epova, Ekaterina N.; Bérail, Sylvain; Zuliani, Tea; Malherbe, Julien; Sarthou, Laurence; Valiente, Manuel; Donard, Olivier F.X.
Highlights: Differentiation of PDO dry-cured ham on the basis of their geographical origin. Multielemental and Sr isotope composition of different dry-cured hams is determined. Multielemental and Sr isotope composition of different mineral salts is provided. Salt is an important contributor to elemental and isotopic composition of ham. Multielements and 87 Sr/ 86 Sr are the promising parameters for origin discrimination. Abstract: We have examined the potential of discriminant inorganic constituents (trace-, ultra-trace elements and Sr isotope ratios) to assess the origin of world famous brands of European dry-cured hams. The variation of the multielemental composition with principal component analysis allowed to discriminate the origin of Bayonne hams. Determined ratio 87 Sr/ 86 Sr was recognized as a strong additional distinctive parameter. The ratio 87 Sr/ 86 Sr allowed to better separate all the different categories of hams in addition to the multi-elemental detection. The major contribution of the value 87 Sr/ 86 Sr for the Bayonne ham is directly related to its curing due to the salt used in process coming from the nearby salt mine Salies-de-Béarn. Since the salt represents around 4% of the final product, it will therefore strongly influence the elemental and isotopic composition of hams. The overall discrimination potential of strontium isotope ratio is evidenced in the final statistical discrimination of the origin of hams.